PENGARUH KOMPETENSI DAN INDEPENDENSI INTERNAL AUDITOR TEHADAP IMPLEMENTASI GOOD CORPORATE GOVERNANCE (Studi Pada Bank BPR Modern Kota Ambon Provinsi Maluku) - Abdullah Sanduan (ITB AAS INDONESIA, 2022)
The purpose of this research is to know and to analyze the influence of competency and independency of the internal auditors to implementation of good corporate governance. Analytical descriptive method used in this research method. The research was conducted in the branch offices of BPR Modern Bank in Ambon City off Maluku. For data analyze and hypothesis testing used by path analysis model to analyze the influence both simultaneously and partially to implementation of good corporate governance in branch offices of Bank in Ambon City off Maluku. The result of this research and hypothesis testing shows that competency and independency of internal auditors both simultaneously and partially have influence to implementation of good corporate governance at branch offices of BPR Modern Bank in Ambon City of Maluku.